2020
DOI: 10.1016/j.jaad.2020.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic predictors to discriminate between in situ and early invasive lentigo maligna melanoma: A retrospective observational study

Abstract: Funding sources: None. Conflicts of interest: None disclosed.IRB approval status: This project was a quality improvement initiative and thus was not formally supervised by our IRB per their policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…At the start of the procedure, the lesion was marked with a margin of 3 mm, marking stiches were placed and the lesion was excised under local anaesthesia. Prior to the procedure, the research physician and the dermatologist with oncologic experience used dermoscopy to mark 0–5 spots within the LM that were suspect for invasive growth using this criteria: homogenous areas, irregular blotches, black colour, obliterated hair follicles and milky red areas 7–9 . In the absence of suspect spots no needle was placed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the start of the procedure, the lesion was marked with a margin of 3 mm, marking stiches were placed and the lesion was excised under local anaesthesia. Prior to the procedure, the research physician and the dermatologist with oncologic experience used dermoscopy to mark 0–5 spots within the LM that were suspect for invasive growth using this criteria: homogenous areas, irregular blotches, black colour, obliterated hair follicles and milky red areas 7–9 . In the absence of suspect spots no needle was placed.…”
Section: Methodsmentioning
confidence: 99%
“…6 Dermoscopy may help differentiating between LM, LMM, other types of melanoma and solar lentigo. [7][8][9] Complete surgical (staged) excision is the best treatment of clinical and biopsy-proven LM 10 as it enables histological examination of the lesion. It allows differentiating between LM and LMM 11 and assesses whether the margins are free of lentigo maligna (melanoma).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Peruilh-Bagolini et al confirmed that gray circles/semicircles and angulated lines are negative predictors of invasive LM while obliterated follicles, irregular blotches, and black color positively predicted invasive LM. These findings are important when incisional biopsies on LM are performed: selecting the area to biopsy with dermoscopy allows to not underestimate the invasive component [86].…”
Section: Melanoma Occurring On Non-facial Chronically Sun Exposed Skinmentioning
confidence: 98%